2017
DOI: 10.17352/ojtm.000004
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma Serostatus in Thai Free- Range Chickens: Prevalence and Two Diagnostic Methods

Abstract: Toxoplasma seroprevalence in free-range chicken, which directly feed from ground, is a good indicator for detecting an environment contamination by T. gondii oocysts. Many serological methods have been used for diagnosing Toxoplasma infection in animals including chicken. Selection of appropriate methods primarily depend on their sensitivity and specifi city as well as laboratory techniques, special reagent or tool requirements and regional prevalence status. The aims of this study were to determine the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Besides, evidence found that infection rate of T. gondii in free range chickens of different part of the world range from 2%-100% (21). The great variations was found as a result of differences in climate changes which has great impact on the lifespan of oocysts, or differences in the used diagnostic techniques, the kind of the samples were depended and seasonality (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, evidence found that infection rate of T. gondii in free range chickens of different part of the world range from 2%-100% (21). The great variations was found as a result of differences in climate changes which has great impact on the lifespan of oocysts, or differences in the used diagnostic techniques, the kind of the samples were depended and seasonality (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…In USA, human toxoplasmosis results in socio-economic loss more than 3.3 billion USD per years ( (Hoffmann et al, 2015). In Bangkok, a previous report showed that 6.4% of cat owners had seropositive for Toxoplasma (Sukthana et al, 2003). In contrast to human, postnatal Toxoplasma infection in cats generally results in non-clinical disease except for immunocompromised cats for example, feline immunodeficiency virus (FIV) and/or feline leukemia virus (FeLV) infected cats and in kitten.…”
Section: Enteric Protozoal Infections In Catsmentioning
confidence: 99%
“…Therefore, cats may not be responsible for a major source of human toxoplasmosis (Jones and Dubey, 2010). In Thailand, prevalence of Toxoplasma seropositive in stray cats in Bangkok are 4.8-11% (Sukthana et al, 2003;Jittapalapong et al, 2007b) whereas cats visiting hospital for any service is 10.1% (Sukhumavasi et al, 2012).…”
Section: Enteric Protozoal Infections In Catsmentioning
confidence: 99%